Effects of maturity at harvest and cultivar on agronomic performance of forage sorghum and the nutritive value of selected sorghum silages - Sonon, R.N.; Suazo, R.; Pfaff, L.; Dickerson, J.T.; Bolson, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
These studies examined the agronomic performance of 20 forage sorghum cultivars, each harvested at three stages of maturity in 1990. Whole-plant dry matter (DM) yields were highest at the late-dough stage of kernel maturity, whereas DM content and grain yields steadily increased as maturity advanced. A voluntary intake and digestion trial was conducted with 12 grain and forage sorghum silages harvested at the late-dough stage in 1989. The highest silage DM intakes and digestibilities were obtained with the high-grain yielding hybrids.
Keywords: Beef; Forage sorghum; Cultivar; Maturity; Intake; Digestibility